Doping Calcia and Yttria into Zirconia Obtained from by Product of Tin Concentrator to Improve its Ionic Conductivity - Fitria Rahmawati; Bambang Prijamboedi; Syoni Soepriyanto; Ismunandar Ismu (Journal of Mathematical and Fundamental Sciences, 2011)
Zirconia has been prepared from Zircon concentrate by caustic fusion methods. Zircon is a by product from tin ore concentration plant at Bangka island of Indonesia. Yttria Stabilized-Zirconia (YSZ) was prepared by introducing the 8 % mol yttrium oxide into zirconia and sintered at 1500 "žaC for 5 hours. In order to obtain constant oxygen vacancy of 8 % mol in Zirconia, an appropriate amount of Yttria and Calcia were introduced into Zirconia and the mixtures were heated at 1350 oC for 5 hours. Elemental composition was determined by SEM/EDX and XRF and lattice parameters were determined using X-ray diffraction method. Ionic conductivity was measured by complex impedance spectroscopy. The results show that doping of Yttria into Zirconia (YSZ) and Calcia-Yttria into Zirconia (CYZ) allows phase transformation of Zirconia from tetragonal with space group P42/nmc into cubic Fm3m and enhance the ionic conductivity. However, the prepared materials are porous and have not met the requirement for the electrolyte material yet.